A Study on the Reservoir Capacity to Control Mud Flood Derived from Mud Volcano: A Phenomenon in Sidoarjo - Mahmud Mustain; Rohmat Ilman Salim; Sholihin Sholihin; Sujantoko Sujantoko (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2010)
This paper is an extended research of Coastal Zone Management of Sidoarjo mud phenomenon. The idea is to find special concept of management to control mud flood using reservoir system. This method, in the mud fluid, is intentionally used to make separation of the solid materials from water. The concept is to calculate sediment velocity in order to find the time of sedimentation then to estimate the volume of mud. Therefore, the reservoir will be determined from this calculation. The result of this research is the dimension of the reservoir: area of 3,704,144.36 m2, the depth of 5.94 m, and the volume 22.018.856.07 m3. The time of sedimentation is calculated of 28.33 hours for 42.2 % of material volume sedimentation. Consequently, the suspension material is 57.8 %. The correction of calculation is depending on the calculation of the velocity of sedimentation, about 2 %.